Crowd medical services in the English Football League: remodelling the team for the 21st century using a realist approach. Issue 12 (21st December 2017) - Leary, Alison; Kemp, Anthony; Greenwood, Peter; Hart, Nick; Agnew, James; Barrett, John; Punshon, Geoffrey
Abstract : Objectives: To evaluate the new model of providing care based on demand. This included reconfiguration of the workforce to manage workforce supply challenges and meet demand without compromising the quality of care. Design: Currently the Sports Ground Safety Authority recommends the provision of crowd medical cover at English Football League stadia. The guidance on provision of services has focused on extreme circumstances such as the Hillsborough disaster in 1989, while the majority of demand on present-day services is from patients with minor injuries, exacerbations of injuries and pre-existing conditions. A new model of care was introduced in the 2009/2010 season to better meet demand. A realist approach was taken. Data on each episode of care were collected over 14 consecutive football league seasons at Millwall FC divided into two periods, preimplementation of changes and postimplementation of changes. Data on workforce retention and volunteer satisfaction were also collected. Setting: The data were obtained from one professional football league team (Millwall FC) located in London, UK. Primary and secondary outcomes: The primary outcome was to examine the demand for crowd medical services. The secondary outcome was to remodel the service to meet these demands. Results: In total, 981 episodes of care were recorded over the evaluation period of 14 years. The groups presenting, demographic and type of presentation did not change over the evaluation. First aiders were involved in 87.7% of episodes of care, nurses in 44.4% and doctors 17.8%. There was a downward trend in referrals to hospital. Workforce feedback was positive. Conclusions: The new workforce model has met increased service demands while reducing the number of referrals to acute care. It involves the first aid workforce in more complex care and key decision-making and provides a flexible registered healthcare professional team to optimise the skill mix of the team.